Impact of Pleistocene–Holocene climate shifts on vegetation and fire dynamics and its implications for Prearchaic humans in the central Great Basin, USA. (27th September 2020) - Brugger, Sandra Olivia; Rhode, David
ABSTRACT: The effects of climate change during the Terminal Pleistocene–Early Holocene transition on ecosystems and early Prearchaic hunter‐gatherers in the central Great Basin of North America are not well understood. We present a palynological reconstruction of regional vegetation and fire history in Grass Valley, central Nevada, from ~14 to ~7.5k cal a BP showing that Pinus ‐dominated woodlands were replaced by dry‐adapted steppe and desert vegetation accompanied by an increase in regional fire activity at the beginning of the Holocene, in response to summer warming and a drying climate. Following a severe drought period peaking ~10.2–9.3k cal a BP, Pinus woodlands partially recovered contemporaneously with the 8.2k cal a BP climate anomaly. Local wetlands provided important resource patches for human foraging societies, and periodic declines of wetlands in response to changing local hydrological conditions may have necessitated adjustments in subsistence and settlement practices and technology.